In‐Season and Carry‐Over Effects of Cover Crops on Productivity and Weed Suppression. (1st July 2016) - Hodgdon, Elisabeth A.; Warren, Nicholas D.; Smith, Richard G.; Sideman, Rebecca G.
Abstract : Data necessary to evaluate cover crop multifunctionality are lacking, particularly for cool, short‐season cropping niches typical of northern New England. We quantified cover crop biomass, weed suppression, and carry‐over effects on subsequent crop and weed growth in 12 winter cover crop treatments {monocrops and mixtures of annual ryegrass [ Lolium multiflorum Lam.], winter rye [ Secale cereale L.], alfalfa [ Medicago sativa L.], crimson clover [ Trifolium incarnatum L.], white clover [ T. repens L.], hairy vetch [ Vicia villosa Roth], soybean [ Glycine max (L.) Merr.], and forage radish [ Raphanus sativus L.], and a weedy fallow [control] treatment}. The forage radish treatments (11 and 28 kg ha −1 seeding rates) were among the highest producers of fall cover crop biomass in all 4 site‐years. The forage radish treatments were also among the most weed‐suppressive in the fall, reducing weed biomass relative to the weedy fallow treatment by 89 to 97% in each of the 4 site‐years. In the spring, annual ryegrass was among the highest (ranging from 349–571 g m −2 across site‐years) and alfalfa was among the lowest (39–287 g m −2 ) biomass‐producing treatments in 3 out of 4 site‐years. Weed biomass in the spring was 73 to 99% lower in annual ryegrass, hairy vetch, and hairy vetch–winter rye mixture treatments than in the weedy fallow treatment. Biomass of the sorghum [ Sorghum bicolor (L.) Moench]–sudangrass [ S. sudanense (Piper) Stapf] phytometer was higher following white clover, hairy vetch, the hairy vetch–rye mixture, and both forage radish treatments compared to following annual ryegrass. Core Ideas Cover crops differ in their ability to provide multiple ecosystem services. This study quantified weed suppression services in 12 cover crop treatments. Weed suppression in fall, spring, and a subsequent phytometer differed among the treatments. Phytometer biomass was higher following forage radish and several legume cover crops compared to annual ryegrass. Cover crop multi‐functionality and tradeoffs were assessed with spider plots.